2019
DOI: 10.1002/jia2.25339
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from suicide among people living with HIV and the general Swiss population: 1988‐2017

Abstract: Introduction In many countries, mortality due to suicide is higher among people living with HIV than in the general population. We aimed to analyse trends in suicide mortality before and after the introduction of triple combination antiretroviral therapy (cART), and to identify risk factors associated with death from suicide in Switzerland. Methods We analysed data from the Swiss HIV Cohort Study from the pre‐cART (1988‐1995), earlier cART (1996‐2008) and later cART (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 33 publications
0
50
1
Order By: Relevance
“…Interestingly, depression, family history of suicide and perceived stigma from living with HIV were found to be associated with suicidal risks in that same study. In a different study, Ruffieux et al (2019) found that high mortality rate because of suicide is often reported amongst PLWHA, especially the very recently diagnosed (HIV-positive diagnosis less than 1 month old) when compared to the general population. Zarei and Joulaei (2018) identified that suicidal ideation was common in both recently and non-recently diagnosed patients with HIV/ AIDS.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Interestingly, depression, family history of suicide and perceived stigma from living with HIV were found to be associated with suicidal risks in that same study. In a different study, Ruffieux et al (2019) found that high mortality rate because of suicide is often reported amongst PLWHA, especially the very recently diagnosed (HIV-positive diagnosis less than 1 month old) when compared to the general population. Zarei and Joulaei (2018) identified that suicidal ideation was common in both recently and non-recently diagnosed patients with HIV/ AIDS.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Despite the availability of ART, suicide rates remained significantly higher in PLHIV than in the general population. [ 35 ] PLHIV facing high levels of HIV-related stigma were more likely to delay enrollment into care than those who did not perceive HIV-related stigma. [ 36 ] To reduce rates of suicide, there is a need to reduce HIV-related stigma and discrimination, provide routine screening and close monitoring for depression and drug and alcohol misuse, and expand the network of psychosocial support.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that people living with the human immunodeficiency virus (PLHIV) are more likely to be depressed than ordinary people due to negative emotions to initial diagnosis, the stress of living with chronic illness, perceived and internalized stigma, and the side effects of HIV drugs [ 1 , 2 , 3 , 4 , 5 ]. The prevalence of depression among PLHIV was between 18% and 81% [ 3 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%